The quantitative soil quality assessment for tobacco plant in Sindoro mountainous zone - Supriyadi, S; Sudaryanto, R; Winarno, J; Hartati, S; Jamil, I S (Journal of Degraded and Mining Lands Management, 2014)
The long-term cultivation of tobacco (Nicotiana tabacum) plant in the Sindoro mountainous zone of Central Java has resulted in soil quality degradation that could affect economic development in the region if sustainable production practices are not identified. The objective of the study was to identify appropriate indicators for assessing soil quality on tobacco plant. The quantitative soil quality indicators were total organic-C, pH, available P and available K (chemical), soil depth, bulk density, AWC (available water capacity) and soil aggregate stability (physical), and qCO2 (soil respiration), MBC (microbial biomass carbon) (biological). The decreases in the soil aggregate stability, available water capacity, cation exchange capacity, soil respiration, microbial biomass carbon and total organic-C; or increases in bulk density (compaction), available P, available K and total nitrogen indicated the decrease in soil quality due to long-term tobacco production. The result of this research showed that the change of soil quality had occurred in Sindoro Mountain. The Soil Quality Index (SQI) for three land use systems in Sindoro mountain (forest, mixed farm, and tobacco) were 0.60, 0.47, and 0.57, respectively. The comparison of these rates with soil quality classes showed that the soil quality presented moderate to good level of quality; class SQI.